Preschool Education in Brazil: Does Public Supply Crowd Out Private Enrollment? - Paulo Bastos; Odd Rune Straume (Inter-American Development Bank (IDB), 2013)
This paper examines whether an expansion in the supply of public preschool crowds out private enrollment, using rich data for municipalities in Brazil from 2000-2006, where federal transfers to local governments change discontinuously with given population thresholds. Results from a regression-discontinuity design reveal that larger federal transfers lead to a significant expansion of local public preschool services, but show no effects on the quantity or quality of private provision. These findings are consistent with a theory in which households differ in willingness to pay for preschool services, and private suppliers optimally adjust prices in response to an expansion of lower-quality, free-of-charge public supply.
Keywords: D12; I21; I28; L21; O15; 330